Pay, Power, and Health: HRI and the Agricultural Conundrum. (September 2019) - Wadsworth, Gail; Courville, Michael; Schenker, Marc
As part of a five-year integrated study on heat-related illness (HRI) among farmworkers in California, the California Institute for Rural Studies (CIRS) convened focus groups with farmworkers in regions of the state where HRI was prevalent. CIRS also interviewed employers and other stakeholders in the state. While this study was not designed to identify causal relationships, we were able to identify patterns of interaction that point to the intersection of agricultural system structures and worker agency in making self-care decisions. Structural categories, such as productivity losses/gains, cut across all self-care choices, often overriding other factors for decision making.